1999
DOI: 10.1161/01.cir.100.10.1056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Candesartan, Enalapril, and Their Combination in Congestive Heart Failure

Abstract: Candesartan alone was as effective, safe, and tolerable as enalapril. The combination of candesartan and enalapril was more beneficial for preventing left ventricular remodeling than either candesartan or enalapril alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 794 publications
(174 citation statements)
references
References 13 publications
5
166
0
3
Order By: Relevance
“…However, mortality was neither a primary nor a secondary endpoint in ELITE. In the RESOLVD [18] study, there was a trend towards better survival with enalapril compared to candesartan (20/327 (6.1%) deaths in the candesartan group compared to 4/109 (3.7%) in the enalapril group, odds ratio 1.71, 95% confidence interval 0.57, 5.12). ELITE II [7], the largest study to date comparing ACE inhibitors and ARBs in CHF using mortality as the primary endpoint, found that the two classes of drugs were similar in their reduction of mortality (hazard ratio comparing losartan to captopril 1.13, 95% confidence interval 0.95, 1.35).…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality was neither a primary nor a secondary endpoint in ELITE. In the RESOLVD [18] study, there was a trend towards better survival with enalapril compared to candesartan (20/327 (6.1%) deaths in the candesartan group compared to 4/109 (3.7%) in the enalapril group, odds ratio 1.71, 95% confidence interval 0.57, 5.12). ELITE II [7], the largest study to date comparing ACE inhibitors and ARBs in CHF using mortality as the primary endpoint, found that the two classes of drugs were similar in their reduction of mortality (hazard ratio comparing losartan to captopril 1.13, 95% confidence interval 0.95, 1.35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several intervention trials have demonstrated that ACEI and/or ARB can decrease morbidity and mortality in CHF [29][30][31], but the a-blocker, doxazosin, one of the most popular a-blockers, was not considered to be a good application for CHF in the ALLHAT trial [32]. As for the change in the plasma BNP level, McKelvie et al have reported that candesartan could decrease the plasma BNP level in the combination with ACEI in patients with CHF [33]. Latini et al have recently shown that valsartan alone, one of the ARBs, could decrease the plasma BNP level at 4 months in patients with symptomatic chronic CHF [34].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is an important issue during a long-term treatment with ACE-I and ARB. 1,[5][6][7][8][9][10][11] Although the mechanisms of ALD breakthrough remain obscure, there was no apparent reduction of the left ventricular mass index (LVMI) in patients with ALD breakthrough(+) during the administration of ACE-I. 8 Aldosterone production in the adrenal gland is mediated mainly by the T-type calcium channel in vitro.…”
Section: Introductionmentioning
confidence: 99%